Integrating formative assessment and participating research: building healthier communities in the CHILE project - Sussman, Andrew L.; Davis, Sally M. (2010)
This article reports a formative assessment process in a large-scale randomized controlled trial in New Mexico aimed at preventing obesity in rural American Indian and Hispanic children in Head Start Programs. We interviewed Head Start Staff and conducted observations to understand the context of food service and physical activity in these sites. We also collected data from other community partners, including grocery store managers and primary care providers, to assess appropriate strategies regarding their engagement in the study. Formative assessment findings helped modify the planned intervention while allowing for variation relevant to cultural and Head Start organizational conditions in each community. Rather than view formative assessment only as a planning phase of the research, our experience illustrates the need to conceptualize these activities more broadly. Integrating formative assessment and participatory research raises the need to address the challenge of ensuring standardization and consistency across varied community settings, the evolving nature of initial formative relationships and the need to build trust in academic/community partnerships. In our work with American Indian and Hispanic communities in New Mexico, formative assessment represents a partnership building opportunity.
Keywords: FORMATIVE ASSESSMENT; RESEARCH